Uptake and Internalization of Exogenous Apolipoprotein E3 by Cultured Human Central Nervous System Neurons - Kieran R. Williams; Ann M. Saunders; Allen D. Roses; Patricia J. Armati (Neurobiology of Disease, 1998)
Apolipoprotein E (apoE) has been confirmed as a risk factor for late-onset Alzheimer's disease (AD) and is associated with neurofibrillary tangles and senile plaques, the microscopic pathological characteristics of AD. There has been no direct evidence that human central nervous system neurons can take up and internalize exogenous apoE, which may be important in order for apoE to be involved in the development of the disease. This paper demonstrates by immunohistochemistry and confocal microscopy that cultured human brain neurons can take up and internalize exogenous recombinant human apoE3. We confirm that neurons express the low-density lipoprotein receptor-related protein (LRP) but do not express the low-density lipoprotein receptor. We also demonstrate that the LRP mediates the neuronal uptake of apoE.